Upaya Peningkatan Tata Kelola Perpustakaan Sekolah Dasar Negeri 69 Balang-Balang Sinjai Barat - Taufiq Mathar; Ainun Wardani; Musdalifah Musdalifah; Marhani Indah Sari; Zulkifli Zulkifli (UPT Perpustakaan UIN Alauddin Makassar, 2021)
Elementary school libraries are an integral part and one of the learning sources in school. Its role in supporting the learning process is highly expected. This paper describes the improvement of library management at SD Negeri 69 Balang-Balang’s Library, West Sinjai, based on the practice of fieldwork carried out for almost a month in the location. During that time, direct observation and interaction with the objects were carried out. As result, generally, some of the objects that have been improved are spatial planning and management of collections and other resources in the library. In addition, the library is also suggested to be able to design programs regarding developing reading interest for the students.